EFECTIVIDAD DE LA ORTODONCIA INTERCEPTIVA EN LA RESOLUCIÓN DE LAS MORDIDAS CRUZADAS UNILATERALES: REVISIÓN NARRATIVA DE LA LITERATURA - Cifuentes-Harris, Carla (2025)
Objective: This study aimed to evaluate the effectiveness of interceptive orthodontics in correcting unilateral posterior crossbite and to describe the available therapeutic alternatives. Materials and Methods: A narrative review was carried out using PUBMED, SCOPUS, and WEB OF SCIENCE databases. The MeSH terms “Interceptive Orthodontics” and “Crossbite,” among others, were employed. After applying inclusion and exclusion criteria, seven studies were selected in accordance with PRISMA guidelines. Results: Rapid Maxillary Expansion (RME) was found to be more effective than Slow Maxillary Expansion (SME) in correcting unilateral posterior crossbite, achieving greater skeletal changes in a shorter period of time. Removable appliances also showed effectiveness, with increases in intercanine width (1.8–3.6 mm) and intermolar width (3.0–4.6 mm), although with lower predictability compared to RME. Treatment adherence and appliance design were identified as influencing factors for treatment outcomes. Conclusion: Interceptive orthodontics is highly effective for the correction of unilateral posterior crossbite, particularly through Rapid Maxillary Expansion. Treatment selection should be based on the individual characteristics of the patient, with long-term follow-up recommended to minimize the risk of relapse.